Sedation in the post-anaesthesia care unit - Macas, Andrius; Andriuškevičiūtė, Lina; Paltanavičiūtė, Jūratė; Slauzgalvytė, Ieva (Acta medica Lituanica, 2012)
Background. Post-anaesthetic sedation is a common practice as it pro vides greater comfort and psychological stability for patients. Some spe cialists claim that sedation in the post-anaesthetic care unit (PACU) is applied too seldom due to several reasons. The goal of this study is to evaluate sedation in PACU in several aspects. Materials and methods. A total of 299 patients admitted to the PACU after general, orthopedic-traumatologic or urologic surgical procedures were enrolled in this prospective study. The patients evaluated their qual ity of sleep and the worst intensity of pain experienced in PACU, which was assessed using the Numerical Rating Scale. Nurses evaluated sedation using the Motor Activity Assessment Scale and filled in the questionnaire about the importance of sedation. Results. Statistically significant difference was observed in the quality of sleep between the patients sedated using benzodiazepines and opioids together and non-sedated patients (p = 0.025). There is no considerable difference in the statistics concerning the behavior of the patients. The patients prescribed only with opioids IV or IM, as well as the patients prescribed with opioids together with benzodiazepines, feel less intense pain compared to the non-sedated patients (p = 0.016, p = 0.03). Accord ing to the personnel, sedation is necessary in PACU. Half of them think that patients prescribed with opioids need additional sedation. Conclusions. Sedation is necessary in PACU. This fact is evident in the statistically significant difference of comfort factors among the patients as well as in the opinion of the nursing personnel that spend most of the time communicating and caring about the comfort of the patients.
Keywords: post-anaesthetic sedation; postoperative care; benzodia zepine; delirium; pain